(untitled) (Journal of Bangladesh Institute of Planners, 2012)
Land reforms in developing countries are an important instrument to reduce social disparities and to launch a desirable social development process. Such reform includes land redistribution amongst the landless. Similarly in Bangladesh, the core element of land distribution is the Khas-land (KL). The results of the empirical studies conducted in the village ‘Shovna’ clearly show that the distribution of KL only superficially follows the legal regulations. In fact, the possibility of a public resource allocation resulting from a broader political-economic consideration cannot be implemented without a considerable degree of collusion and interdependence between local and national elites in Bangladesh. Journal of Bangladesh Institute of Planners Vol. 5, Dec 2012, pp. 25-36